THG113.31, a specific PGF2alpha receptor antagonist, induces human myometrial relaxation and BKCa channel activation - Morrison John J; Sexton Donal J; O'Reilly Michael J; Doheny Helen C (BMC, 2007)
Abstract Background PGF2alpha exerts a significant contractile effect on myometrium and is central to human labour. THG113.31, a specific non-competitive PGF2alpha receptor (FP) antagonist, exerts an inhibitory effect on myometrial contractility. The BKCa channel is ubiquitously encountered in human uterine tissue and plays a significant role in modulating myometrial cell membrane potential and excitability. The objective of this study was to investigate potential BKCa channel involvement in the response of human myometrium to THG113.31. Methods Single and whole-cell electrophysiological BKCa channel recordings from freshly dispersed myocytes, were investigated in the presence and absence of THG113.31. Functional studies investigated the effects of THG113.31 on isolated spontaneous myometrial contractions, in the presence and absence of the BKCa channel blocker, iberiotoxin. Results Single channel recordings identified the BKCa channel as a target of THG113.31. THG113.31 significantly increased the open state probability of these channels [control 0.023+/-0.006; 10 microM THG113.31 0.087+/-0.012 (P = 0.009); and 50 microM THG113.31 0.1356+/-0.018 (P = 0.001)]. In addition, THG113.31 increased whole-cell BKCa currents over a range of membrane potentials, and this effect was reversed by 100 nanoM IbTX. Isometric tension studies demonstrated that THG113.31 exerted a significant concentration-dependent relaxant effect on human myometrial tissue and pre-incubation of strips with IbTX abolished this effect on spontaneously occurring contractions. Conclusion These data suggests that activation of the BKCa channel may contribute, at least partially, to the uterorelaxant effect of THG113.31.